New Metabolites and Bioactive Actinomycins from Marine-Derived Streptomyces sp. ZZ338 - Zhang, Xiufang (Mar Drugs, 2016)
An extract prepared from the culture of a marine-derived actinomycete Streptomyces sp. ZZ338 was found to have significant antimicrobial and antiproliferative activities. A chemical investigation of this active extract resulted in the isolation of three known bioactive actinomycins (1–3) and two new metabolites (4 and 5). The structures of the isolated compounds were identified as actinomycins D (1), V (2), X(0β) (3), 2-acetylamino-3-hydroxyl-4-methyl-benzoic acid methyl ester (4), and N-1S-(4-methylaminophenylmethyl)-2-oxo-propyl acetamide (5) based on their nuclear magnetic resonance (NMR) and high resolution electrospray ionization mass spectroscopy (HRESIMS) data as well as their optical rotation. This class of new compound 5 had never before been found from a natural resource. Three known actinomycins showed activities in inhibiting the proliferation of glioma cells and the growth of methicillin-resistant Staphylococcus aureus, Escherichia coli, and Candida albicans and are responsible for the activity of the crude extract. Actinomycin D (1) was also found to downregulate several glioma metabolic enzymes of glycolysis, glutaminolysis, and lipogenesis, suggesting that targeting multiple tumor metabolic regulators might be a new anti-glioma mechanism of actinomycin D. This is the first report of such a possible mechanism for the class of actinomycins.